May Covid-19 cause intracerebral hemorrhage in patients with cavernous malformation? - Şahin, Ali; Oral, Şükrü; Eren, Esma (Journal of Surgery and Medicine, 2020)
Coronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 virus, has become a global health threat. COVID-19 often involves the respiratory tract, however, it is also associated with several neurological conditions (seizures, convulsions, changes in consciousness, encephalitis, cerebral hemorrhage, and cerebral thrombosis). Cavernous malformations (CMs) are vascular lesions that occur in the central nervous system and the body. Symptomatic CMs most manifest through headaches, seizures, hemorrhage, or focal neurological deficits. The co-occurrence of COVID-19 and cavernous hemangioma hemorrhage has not been reported in the literature. The association between COVID-19 and intracerebral hemorrhage remains controversial. However, a relationship with COVID-19 infection in patients with intracerebral hemorrhage should always be considered during this pandemic. The case of a 37-year-old female patient is reported here. The patient presented to the emergency room with a headache that persisted for 2 days along with cavernous hemangioma hemorrhage and tested positive for COVID-19.